التغير الاجتماعي ـ مدخل نظري ـ - مومن بكوش, الجموعي (جامعة الوادي - University of Eloued, 2018)
إن المتأمل في واقعنا المعاش يشهد حالة من التبدل والتحول طغت على العديد من المجالات الاجتماعية والثقافية والأسرية والتكنولوجية والسياسية والاقتصادية والتعليمية والنفسية ...، هذه الظاهرة يطلق عليها المختصون في مجال العلوم الاجتماعية والنفسية بالتغير الاجتماعي،ومن أجل معرفة هذه الظاهرة فهما علميا و دقيقا جاءت هذه المداخلة النظرية ليتم من خلالها تقديم نظرة شاملة حول ظاهرة التغير الاجتماعي ومختلف الأبعاد الكامنة خلفها والمتفاعلة فيما بينها من خلال حصر ومناقشة مختلف النظريات المفسرة لهاته الظاهرة،وتوضيح مختلف الصعوبات والعوائق الاجتماعية والمادية التي تقف خلفها .The contemplator in our reality is witnessing a state of change and transformation that has overwhelmed many social, cultural, family, technological, political, economic, educational and psychological fields ... This phenomenon is called by specialists in the field of social and psychological sciences with social change and in order to know this phenomenon scientifically and accurately. The theoretical intervention is to provide an overview of the phenomenon of social change and the various dimensions behind it and interacting with each other through the enumeration and discussion of different theories explaining the phenomenon, and clarify the various difficulties and social obstacles and The material that stands behind it.
Social change -Theoretical entrance
مقال
Keywords: التغير الاجتماعي،التقدم الاجتماعي،التنمية الاجتماعية،التطور الاجتماعي،النمو الاجتماعي التحديث .; Social change, social progress, social development, social development, social growth, modernization.